Geotechnical Properties of Certain Iraqi Carbonate Rocks - Ali, Salahalddin Saeed (Sulaimani Journal for Pure and Applied Sciences, 2001)
Petrography and some geotechnical ail properth properties of certain Iraqi carbonate rocks belonging to (8) geologic formations from (10) locations, were studied in lab. The influence of petrography and water saturation on the engineering properties was investigated, Correlation between different physical and mechanical properties was achieved. Finally a proposed engineering classification based on (bulkidensity, compressional wave velocity. dynamic modulus of elasticity. uniaxial comparative strength and brazillian tensile strength) for the studied rocks was established it is concluded that ti e studied carbonate rocks can be !divided thy groups according to shay physical and mechanical propertiest they are r u strength, medium to high strength (4.1- low to medium strength) rocks.
Keywords: Rock Mechanic; Limestone; Physice71 PronertiesDamask hbopertii Petrograph; Water Saturation